The Relationship Between Body Weight and Egg Weight of Padjadjaran Quails of Layer and Broiler Types - Sujana, Endang; Indrijani, Heni; Nugraha, Achmad Nugraha Trieandi; Hidayatullah, Syarif; Rahmat, Dedi (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
The study investigating the relationship between body weight and egg weight in Padjadjaran quails, encompassing both layer and broiler types, was conducted at the Quail Breeding Center within the Faculty of Animal Husbandry at Universitas Padjadjaran. The research involved 100 female quails, consisting of 50 from each type, all of which were 15 weeks old, along with their eggs. The primary aim was to assess the strength and nature of the relationship between body weight and egg weight in these quails. A correlational method was employed for the analysis. The findings revealed a strong correlation between body weight and egg weight in Padjadjaran layer quails, indicated by a correlation coefficient of 0.792. The relationship was represented by the regression equation \( y = 0.0586x + 0.8429 \), which had a relatively high coefficient of determination (\( R^2 \)) of 0.6281. Conversely, the results for Padjadjaran broiler quails indicated a weak correlation, with a correlation coefficient of 0.374. The regression equation for broiler quails was \( y = 0.0145x + 8.0157 \), exhibiting a low coefficient of determination (\( R^2 \)) of 0.1402. In conclusion, the study identified a strong correlation between body weight and egg weight for Padjadjaran layer quails, while a weak correlation was observed for Padjadjaran broiler quails. Furthermore, the regression equation for predicting egg weight based on body weight is deemed reliable for Padjadjaran layer quails but not applicable to broiler quails, as the low determination value suggests that the regression model for broiler quails is insufficient for such predictions.